Efeitos de fontes lipídicas em dietas para frangos de corte sobre o desempenho, rendimento e composição da carcaça - Felipe Diniz Duarte (2007)
An experiment was carried out with 1,782 one-day-old Cobb lineage males chicks aiming to evaluate the effect of adding different fats sources (tallow, poultry fat, degommed soybean oil and mixes of tallow plus degommed soybean oil and tallow plus poultry fat) in their diets on performance, yielding and carcass composition. The chicks were housed in a poultry facility, with 11 birds/m². The treatments were defined with variations of the type of the fat source in the diets and enabling that all of them presented the same level of metabolizable energy (ME) obtained from the lipidic source, as the following: Treatment 1 – tallow, 100% ME; Treatment 2 – poultry fat, 100% ME; Treatment 3 – degommed soybean oil, 100% ME; Treatment 4 – degommed soybean oil and tallow, comprising 25 and 75% of the ME, respectively; Treatment 5 – degommed soybean oil and tallow, comprising 50 and 50% of the ME, respectively; Treatment 6 – degommed soybean oil and tallow, comprising 75 and 25% of the ME, respectively; Treatment 7 – poultry fat and tallow, comprising 25 and 75% of the ME, respectively; Treatment 8 – poultry fat and tallow, comprising 50 and 50% of the ME, respectively and Treatment 9 – poultry fat and tallow, comprising 75 and 25% of the ME, respectively. The birds were raised from 1 to 41 day-old. The rations for each phase (initial 1-21 day-old; growth 22-36 day-old and finishing 37-41 day-old) were isocaloric and isonutritive and offered ad libitum. The ME levels of the rations were: initial 2,950 Kcal/Kg, growth 3,100 Kcal/Kg and finishing 3,180 Kcal/Kg. The statistical design was the complete randomized divided in nine treatments with six repetitions. The differences between the means were compared by the “Student-Newman-Keuls¨ (SNK) test. The broiler chickens fed poultry fat and tallow, with 50% of the ME obtained from each lipidic source (treatment 8) showed worse feed conversion (p<0.05) than those fed degommed soybean oil, 100% ME (treatment 3) and degommed soybean oil and tallow, comprising 75 and 25% of the ME, respectively (treatment 6). There was no difference (p>0.05) for the feed conversion regarding the former three treatments previously cited in relation to the others. Also, differences were not found (p>0.05) regarding the others variables of performance (live weight and ration consumption) as well as for yielding (whole carcass, cuts and abdominal fat) and composition (moisture, crude protein, ether extract and ashes) of the carcasses.